Intensity Ratio of LH2 Complexes from Rhodopseudomonas palustris and Rhodobacter sphaeroides for Purity Determination - Prihastyanti, Monika NU; Kurniawan, Jovine M; Yusuf, Melisa M; Azmi, Sherly S; Ilmi, Mustafavi C; Indarto, Michelle L; Hoetomo, Stefan C; Wijaya, Melina E; Jatiyati, Greta; Brotosudarmo, Tatas H.P.; Heriyanto, Heriyanto (Indonesian Journal of Natural Pigments, 2020)
Purification procedures to obtain light-harvesting complexes were performed on two photosynthetic bacteria, i.e. Rhodospseudomonas (Rps.) palustris and Rhodobacter (Rb.) sphaeroides. In this study, purification was initially carried out using series of centrifugation towards the bacteria cell to acquire chromatophore of the bacteria. Application of detergent (lauryldimethylamine oxide, or LDAO) to the chromatophore enabled the extraction of membrane containing photosynthetic apparatus. Further purification involved the application of sucrose density gradient centrifugation and ion exchange chromatography. The purity of collected LH2 complexes can be determined by calculating the ratio of AB850 : Aprotein. The resulting LH2 complexes from both bacteria showed relatively high ratio suggesting the purity of the complexes.